Analisis Sejarah Jami Jobang dalam Randai Masyarakat Bukik Gadang, Sawahlunto - Septri .; Fauzan Oktavionda; Abimanyu Satria Maulana; Mimi Sri Fala; Shabbyah Gheitsa Nasywa; Fikri Ali Candra; Jumadil Aqshar; Rizka Akmalia Putri Harahap; Devigo Arifandi; Novia Apriasari (CV. ITTC INDONESIA, 2026)
The main problem addressed in this activity is the lack of proper documentation of the local story of Jami Jobang, which is still preserved in the collective memory of the Bukik Gadang community, Talawi District, Sawahlunto City, and has not been optimally introduced to younger generations. This activity aims to analyze the history of Jami Jobang as a local story, identify the cultural values contained in it, and explain its adaptation into a community randai performance as an effort to preserve oral tradition. The method used in this activity is a descriptive-participatory method through randai script study, field observation, documentation, informal interviews with the community, and a visit to the burial site of one figure related to the Jami Jobang story. The data were analyzed using qualitative descriptive analysis by interpreting field data, community narratives, documentation, and elements of the randai performance to discover the historical meaning and cultural values contained in the story. The results show that Jami Jobang is not only a tragic folk story but also a cultural narrative containing customary, moral, religious, social, and educational values. The adaptation of Jami Jobang into randai shows that traditional performing arts can serve as a medium for preserving local history, transmitting cultural values, and strengthening the identity of the Bukik Gadang community.